2013
DOI: 10.1371/journal.pone.0083656
|View full text |Cite
|
Sign up to set email alerts
|

Fornix-Based versus Limbus-Based Conjunctival Flap in Trabeculectomy: A Quantitative Evaluation of the Evidence

Abstract: ObjectiveTo evaluate the efficacy and tolerability of limbus-based (LBCF) compared with fornix-based conjunctival flaps (FBCF) for trabeculectomy in the treatment of patients with uncontrolled glaucoma.MethodsA comprehensive literature meta-analysis was performed according to the Cochrane Collaboration methodology to identify controlled clinical trials comparing LBCF with FBCF in trabeculectomy. The efficacy measures were the weighted mean differences (WMDs) for intraocular pressure reduction (IOPR), the reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…Our study showed that conjunctival flap method did not have a significant impact on bleb survival in the rabbit model. The results of our study fall in line with previous retrospective human studies [ 6 , 18 20 ] which showed no major differences in efficacy between the two methods. It appears that surgical skill and preference are the main factors that should determine conjunctival flap approach in the rabbit model.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that conjunctival flap method did not have a significant impact on bleb survival in the rabbit model. The results of our study fall in line with previous retrospective human studies [ 6 , 18 20 ] which showed no major differences in efficacy between the two methods. It appears that surgical skill and preference are the main factors that should determine conjunctival flap approach in the rabbit model.…”
Section: Discussionsupporting
confidence: 92%
“…The authors’ reported means and standard deviations (SD) of the IOPR were directly used. When these were not available, they were computed as follows: IOPR = IOP baseline - IOP endpoint , SD IOPR = (SD baseline 2 + SD endpoint 2 - SD baseline × SD endpoint ) 1/2 [ 19 ]. The secondary outcome measure was the difference in reduction between glaucoma medications.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous meta-analysis report about limbus- and fornix-based trabeculectomies, IOP reduction appeared to be the same or superior in limbus-based trabeculectomy 13 . If the difference of the rates of surgical failure was 20%, the minimum sample size was calculated to be 151 eyes with a one-sided significance level of 0.05 and a power of 0.8.…”
Section: Methodsmentioning
confidence: 83%
“…By contrast, avascular and cystic blebs created by limbus-based trabeculectomy procedures may contribute to the surgical outcome in these cases. Although there are many retrospective and prospective studies about the comparison of surgical outcomes between limbus- versus fornix-based trabeculectomy, most of the studies have not shown significant better surgical outcomes with limbus-based trabeculectomy than fornix-based trabeculectomy 13 14 15 16 17 18 19 20 21 22 23 24 . This may be due to the small sample size or the use of patients with various backgrounds that comprised low and high risk factors.…”
mentioning
confidence: 99%